Iris-Occlusion of XEN Gel Stent following Ab Externo Transconjunctival Implantation Technique - Sunil Ruparelia; Nir Shoham-Hazon (Case Reports in Ophthalmological Medicine)
The use of minimally invasive glaucoma surgery (MIGS) devices has become increasingly common for the management of elevated intraocular pressure (IOP) in the context of glaucoma. These technologies have traditionally been associated with fewer postoperative complications than conventional surgical techniques. However, we report on a rare case of transient XEN occlusion associated with pupil dilation following XEN gel stent implantation. This case highlights that in future XEN implantations, it may be preferable to position the XEN at a lesser angle to the iris to prevent such an occlusion. The use of different positionings of XEN is performed to optimize outcomes. However, it is highlighted that complications may arise in certain circumstances.